PEMBERIAN DAN PENGAWASAN IZIN TINGGAL TERBATAS KANTOR IMIGRASI KELAS I DENPASAR TERHADAP TENAGA KERJA ASING DI DENPASAR - Nababan, Pattun; Wairocana, I Gusti Ngurah; Hadjon, Edward Thomas Lamury (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
To carry out the functions of immigration, The Government of Indonesia setselective policy against foreigners including foreign worker who intend to work andenter Indonesia’s teritory. To support the policy, it is necessary setting, restrictions, andservices like limited stay permit granting. In order to prevent or reduce immigrationviolations, it is necessary instrument of the immigration law enforcement byimmigration control and immigration action.